Progesterone Receptor Action in Leiomyoma and Endometrial Cancer - Kim, J. Julie (2009)
Progesterone is a key hormone in the regulation of uterine function. In the normal physiological context, progesterone is primarily involved in remodeling of the endometrium and maintaining a quiescent myometrium. When pathologies of the uterus develop, specifically, endometrial cancer and uterine leiomyoma, response to progesterone is usually altered. Progesterone acts through mainly two isoforms of the progesterone receptor (PR), PRA and PRB which have been reported to exhibit different transcriptional activities. Studies examining the expression and function of the PRs in the normal endometrium and myometrium as well as in endometrial cancer and uterine leiomyoma are summarized here. The clinical use of progestins and the transcriptional activity of the PR on genes specific to endometrial cancer and leiomyoma are described. An increased understanding of the differential expression of PRs and response to progesterone in these two diseases is critical in order to develop more efficient and targeted therapies.